Identification and Validation of miRNA-TF-mRNA Regulatory Networks in Uterine Fibroids - Peng, Xiaotong; Mo, Yanqun; Liu, Junliang; Liu, Huining; Wang, Shuo (Frontiers in Bioengineering and Biotechnology, 2022)
Uterine fibroids (UF) is the most common benign gynecologic tumor and leads to heavy menstrual bleeding, severe anemia, abdomen pain, and infertility, which seriously harm to women health. Unfortunately, the regulatory mechanisms of UF have not been elucidated. Recent studies have demonstrated that miRNAs play a vital role in the development of uterine fibroids. As a high throughput technology, microarray is utilized to identify differentially expressed genes (DEGs) and miRNAs (DEMs) between UF and myometrium. We identified 373 candidate DEGs and top 100 DEMs. Function enrichment analysis showed that candidate DEGs mainly enriched in biological adhesion, locomotion and cell migration, collagen containing extracellular matrix. Subsequently, protein-protein interaction (PPI) networks are constructed to analyze the functional interaction between DEGs and screen hub DEGs. Subsequently, the expression levels of hub DEGs were validated by real-time PCR of clinical UF samples. The DGIdb database was used to select candidate drugs for hub DEGs. Molecular docking was applied to test the affinity between proteins and drugs. Furthermore, target genes for 100 candidate DEMs were predicted by miRwalk3.0. After overlapping with 373 candidate DEGs, 28 differentially expressed target genes (DEGTs) were obtained. miRNA-mRNA network was constructed to investigate the interactions between miRNA and mRNA. Additionaly, two miRNAs (hsa-miR-381-3p and hsa-miR-181b-5p) were identified as hub DEMs. In order to better elucidate the pathogenesis of UF and synergistic effect between miRNA and transcription factor (TF), we constructed miRNA-TF-mRNA regulatory network. Meanwhile, in vitro results suggested that dysregulated hub DEMs were associated with the proliferation, migration and apoptosis of UF cells. Our findings provided a novel horizon to reveal the internal mechanism and novel targets for the diagnosis and treatment of UF.